Automated Measurement of Colorectal Polyp Height at CT Colonography: Hyperplastic Polyps are Flatter than Adenomatous Polyps - Summers, Ronald M. (2009)
OBJECTIVE: It is known that hyperplastic polyps are more difficult to detect than adenomatous polyps at CT colonography (CTC) and it has been theorized that this is because hyperplastic polyps are flatter. Using automated software that computes polyp height, we determined whether hyperplastic colonic polyps on CTC are indeed flatter than adenomatous polyps of comparable width. MATERIALS AND METHODS: 1186 screening patients at 3 medical centers underwent oral contrast-enhanced CTC and same-day optical colonoscopy (OC) with segmental unblinding. 185 of the patients had at least one hyperplastic or adenomatous polyp 6–10 mm in size visible at CTC, where size was determined by a calibrated guidewire at OC. To assess flatness, the heights of the polyps at CTC were measured using a validated automated software program. Heights and height-to-width ratios of the hyperplastic polyps were compared to those of the adenomatous polyps using a t-test (two-tailed, unpaired, unequal variance). RESULTS: There were 176 adenomatous and 83 hyperplastic polyps visible at segmentally unblinded OC. The fraction of these polyps that were measurable at CTC using the automated software was not significantly different for adenomatous versus hyperplastic polyps (158/176, 89.8% versus 73/83, 83.9%, p=0.2). The average height-to-width ratios using automated width measurements were 15% less for hyperplastic polyps: 0.39±0.20 (n=158) and 0.33±0.19 (n=73) for adenomatous and hyperplastic polyps, respectively (p=0.03). When polyps of comparable OC size or CTC width were considered, the heights of hyperplastic polyps were up to 27% less than those of adenomatous polyps. CONCLUSIONS: For 6–10 mm polyps of a given size as determined by optical colonoscopy or a given width at CT colonography, hyperplastic polyps tend to be flatter (i.e., have lower height) compared to adenomatous polyps.